2015
DOI: 10.1039/c5py01367d
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable, eco-friendly polyesters synthesized from renewable resources: preparation and thermal characteristics of poly(dimethyl-propylene furanoate)

Abstract: 16Poly(2,2-dimethyl-1,3-propylene furanoate) (PDMPF), an interesting sustainable biobased 17 polyester based on 2,5-furan dicarboxylic acid (FDCA), was synthesized by applying the 18 two-stage melt polycondensation method. The polyester exhibited a melting temperature of 19 T m =198 o C and a glass transition temperature of T g =68 o C. Multiple melting was observed for 20 the samples crystallized isothermally at temperatures ranging from 160 to 175 o C. Extensive 21 recrystallization was evidenced by modulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 61 publications
4
51
1
Order By: Relevance
“…Before the SSP treatment all materials were studied with TGA in order to evaluate their thermal stability and mainly their decomposition initiation temperature. As can be seen in Figure , PEF and its nanocomposites are very stable since their decomposition starts above 350 °C, which is in well agreement with our previous studies . Furthermore, as can be seen, the differences between neat PEF and its nanocomposites containing SiO 2 or TiO 2 are negligible, which is an indication that the addition of both nanofilles does not affect the thermal stability of PEF.…”
Section: Resultssupporting
confidence: 90%
“…Before the SSP treatment all materials were studied with TGA in order to evaluate their thermal stability and mainly their decomposition initiation temperature. As can be seen in Figure , PEF and its nanocomposites are very stable since their decomposition starts above 350 °C, which is in well agreement with our previous studies . Furthermore, as can be seen, the differences between neat PEF and its nanocomposites containing SiO 2 or TiO 2 are negligible, which is an indication that the addition of both nanofilles does not affect the thermal stability of PEF.…”
Section: Resultssupporting
confidence: 90%
“…The first two polyesters (PEF, PPF) show excellent gas barrier, mechanical and thermal properties, superior than those of the corresponding polyesters based on terephthalic acid, poly(ethylene terephthalate) (PET), and poly(propylene terephthalate) (PPT) . There exist few studies on copolymers and nanocomposites based on PEF, PPF, and PBF, as well as a few PAFs . Surprisingly, blends of these compounds attracted much less attention (to the best of our knowledge, only two studies reported on PBF/PLA blends).…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolysis gas chromatography/mass spectrometry was used to characterize the pyrolyzates of 3001‐OH, PU‐0, and PU‐21 samples to identify the individual fragments and obtain structural information concerning their decomposition mechanism. The pyrolysis temperature is chosen at 500°C because it is close to the fully decomposed temperature of aliphatic polyesters and bisphenol A‐based polymers . The chromatograms of pyrolysis products at 500°C and their identifications are shown in Figure and Tables and , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The pyrolysis temperature is chosen at 500°C because it is close to the fully decomposed temperature of aliphatic polyesters and bisphenol A-based polymers. [36][37][38] The chromatograms of pyrolysis products at 500°C and their identifications are shown in Figure 12 and Tables 7 and 8, respectively. Figure 12A shows that in low retention times (Rt) at 1.84 and 2.52 minutes, 3001-OH molecules were decomposed into the fragments with m/z at 58 and 72 assigned to acetone, propionaldehyde, and 2-oxopropanal, respectively, which come from the thermal decomposition of poly(oxypropylene) chains in the 3001-OH.…”
Section: Analysis Of Flame Retardant Mechanism In Gaseous Phasementioning
confidence: 99%